Examining the Approaches of Customer Segmentation in a Cosmetic Company: A Case Study on L'oreal Malaysia SDN BHD - Ong, Poh Choo (2010)
Purpose – The purpose of this study is to examine the market segmentation approaches available and identify which segmentation approaches best suit for L’Oreal Malaysia. Design/methodology/approach – Questionnaires were distributed to 80 L’Oreal cosmetic users in Malaysia and 55 completed questionnaires were analyzed. Besides, two interviews being conducted at L’Oreal Malaysia office and the result were analyzed too. Findings – The results were as follows. First, analysis of L’Oreal cosmetic users based on segmentation bases available from different age group of users to generating segmentation variable that deemed appropriate to L’Oreal Malaysia. Second, analysis from L’Oreal Malaysia, the company perspectives of segmentation to accurately define the segmentation methods best fit into the company’s marketing program. Practical implications – Although market segmentation is one of the most established concepts in marketing, still there are some shortfalls in the body of research creating a gap between theory and practice which lead to failure in the implementation of segmentation. (Sausen et al., 2005) Nonetheless, segmentation has been extensively used in consumer marketing. Effective segmentation is possible with conditions that segment is measurable, accessible, substantial and homogeneous. Originality/value - The study has originality and values in that segmentation concept have not been studies much in the cosmetic domain in Malaysia.